High Fat Diet Modulates Trypanosoma cruzi Infection Associated Myocarditis - Nagajyothi, Fnu (Public Library of Science, 2014)
BACKGROUND: Trypanosoma cruzi, the causative agent of Chagas disease, has high affinity for lipoproteins and adipose tissue. Infection results in myocarditis, fat loss and alterations in lipid homeostasis. This study was aimed at analyzing the effect of high fat diet (HFD) on regulating acute T. cruzi infection-induced myocarditis and to evaluate the effect of HFD on lipid metabolism in adipose tissue and heart during acute T. cruzi infection. METHODOLOGY/PRINCIPAL FINDINGS: CD1 mice were infected with T. cruzi (Brazil strain) and fed either a regular control diet (RD) or HFD for 35 days following infection. Serum lipid profile, tissue cholesterol levels, blood parasitemia, and tissue parasite load were analyzed to evaluate the effect of diet on infection. MicroPET and MRI analysis were performed to examine the morphological and functional status of the heart during acute infection. qPCR and immunoblot analysis were carried out to analyze the effect of diet on the genes involved in the host lipid metabolism during infection. Oil red O staining of the adipose tissue demonstrated reduced lipolysis in HFD compared to RD fed mice. HFD reduced mortality, parasitemia and cardiac parasite load, but increased parasite load in adipocytes. HFD decreased lipolysis during acute infection. Both qPCR and protein analysis demonstrated alterations in lipid metabolic pathways in adipose tissue and heart in RD fed mice, which were further modulated by HFD. Both microPET and MRI analyses demonstrated changes in infected RD murine hearts which were ameliorated by HFD. CONCLUSION/SIGNIFICANCE: These studies indicate that Chagasic cardiomyopathy is associated with a cardiac lipidpathy and that both cardiac lipotoxicity and adipose tissue play a role in the pathogenesis of Chagas disease. HFD protected mice from T. cruzi infection-induced myocardial damage most likely due to the effects of HFD on both adipogenesis and T. cruzi infection-induced cardiac lipidopathy.